Corporate Social Responsibility: Best Practices and Industry Comparisons - Muslim, Muslim; Pelu, Muhammad Faisal AR (The Journal of Business and Management Research, 2023)
Objectives: This study examines best practices of Corporate Social Responsibility (CSR) across various industries, focusing on environmental sustainability, ethical labor practices, community engagement, and transparent governance. Research Design and Methodology: A mixed-methods approach was employed, integrating quantitative data from a survey of 300 companies and qualitative insights from 20 in-depth interviews with CSR managers, employees, and community representatives. This comprehensive methodology provides a nuanced understanding of CSR practices and their impacts across different sectors. Findings and Discussion: The study reveals that 78% of companies have implemented significant environmental initiatives, such as reducing carbon emissions and promoting sustainable sourcing. Ethical labor practices are emphasized by 85% of companies, ensuring fair wages and safe working conditions. Community engagement initiatives, like Microsoft's YouthSpark and Coca-Cola's 5by20 programs, demonstrate substantial contributions to educational and economic development. Transparent governance, as practiced by companies like Nestlé and Procter & Gamble, builds stakeholder trust and accountability. The comparative analysis underscores industry-specific CSR strategies, with technology companies focusing on digital inclusion and consumer goods companies emphasizing sustainability. Implications: The findings suggest that effective CSR practices are integral to enhancing business performance and societal well-being. Companies can leverage these insights to integrate CSR into their core strategies, fostering innovation, competitiveness, and long-term sustainability. This study contributes to the growing body of evidence that CSR is a strategic imperative, urging businesses to adopt comprehensive and context-specific CSR practices to meet evolving stakeholder expectations and create positive societal impacts.